Development of a microalgal process for municipal wastewater treatment with concurrent nutrients recovery and reduced carbon emission - Tan, Wei Jen (Nanyang Technological University, 2022)
The objective of this project is to investigate the use of microalgae as an alternative approach for the treatment of wastewater. And compare it with current biological nitrogen removal (BNR) processes in terms of nutrients recovery and carbon emissions.